Strategi Kebijakan Pembangunan Aplikasi Penyampaian Informasi Perkuliahan Berbasis Sms Gateway Pada Sekolah Tinggi Keguruan Dan Ilmu Pendidikan (Stkip Pgri Pacitan) - Setiawan, Budi; ., Maryono; ., Sukadi; Purnama, Bambang Eka (Speed - Indonesian Journal on Computer Science, 2014)
Abstract: IN STKIP PGRI PACITAN still in the process of lecture information on paste on the notice board. To be able to view information lecturing students sometimes make a long queue waiting to get that information. To facilitate students in getting the campus information system invented sms based information that can be accessed from anywhere 24 hours. This system aims to produce application-Based Information Systems course and SMS Gateway Makes it easy for students to view course information. The method used in this research are methods Library, observations, interviews, data analysis, system design, programming, testing and implementation program. Hasil dari penelitian ini adalah Dengan adanya sistem informasi berbasis SMS GatewayÂ  ini pihak BAAK STKIP PGRI PACITAN lebih mudah dalam penyampaian informasi kepada mahasiswa. Berdasarkan pendapat dari 30 responden dengan berbagai pertanyaan yang meliputi kualitas sistem berbasis sms, kemampuan sistem demi membantu mendapatkan informasi, tingkat kemudahan dan kecepatan proses Sistem Informasi berbasis sms gateway dihasilkan bahwa rata-rata 85% â 90% responden sangat appreciate terhadap Sistem Informasi Berbasis SMS Gateway. Keyword / Key word: Information Systems, SMS gateway, STKIP PGRI PACITAN